Linearity and carryover of automated hematology counter Horiba® Abx Micros ESV 60 - Cruz, Nathan R.N. [UNESP] (2018)
The automated hematology counter ABX Micros 60 ESX (Horiba Medical 2012) is veterinary hematology analyzer multi-species that carries 50 counts per hour releases 18 blood parameters, in addition to graphical representations (histograms) for leukocytes, erythrocytes and platelets. The objective of this study is to evaluate the performance of the apparatus with respect to linearity and carryover through commercial control and blood samples from the routine of Veterinary Clinical Pathology Laboratory. According to results we can say that this device has excellent linearity coefficient (r2=0.99) in leukocyte parameters, erythrocytes and platelets during that time dilutions. Regarding the carryover was excellent device performance, however, was not in conformity values in the parameters of MCHC and VPM in one of the methodologies made that can be justified by the limited formula that does not consider the equipment characteristics.